Optimization of Phytochemicals Extraction from Fennel (Foeniculum Vulgare) Seeds using Response Surface Methodology - Upadhyay, Sushmita; Shiwakoti, Shreejana; Maskey, Bunty (Tribhuvan University Journal of Food Science and Technology, 2024)
Phytochemicals are bioactive chemical compounds found in plants considered to be beneficial to human health. The study aimed to optimize the extraction parameters for phytochemical compounds from fennel seeds using response surface methodology (RSM) based on Box-Behnken Design (BBD). Ethanol concentrations (40%, 60%, and 80%), extraction times (90, 120 and 150 min), and temperatures (30, 50, and 70°C) were selected and optimized to get higher extraction efficiency. The effects of major extraction variables on the levels of phenolic compounds, flavonoids, and antioxidant activity in the extracts were evaluated. Based on these findings, optimal operating conditions were identified to maximize the recovery of these bioactive compounds. Analysis of variance (ANOVA) was applied, and the significant effects of the factors and their interactions were tested at a 95% confidence interval. The optimum conditions obtained using RSM were ethanol concentration of 78%, a temperature of 59.8°C, and a time of 90 min. The phytochemicals were recovered using an optimized system to 48.117 mg GAE/g of total phenolic content (TPC), 17.732 mg QE/g of total flavonoid content (TFC) and 74.14% of antioxidant activity (AA). Hence, solvent extraction is an effective and economically viable method for recovering phytochemicals from fennel seeds.